2017
DOI: 10.18632/oncotarget.18820
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial profile analysis by MiSeq sequencing of pancreatic carcinoma patients in China

Abstract: Pancreatic carcinoma (PC) is a lethal cancer. Gut microbiota is associated with some risk factors of PC, e.g. obesity and types II diabetes. However, the specific gut microbial profile in clinical PC in China has never been reported. This prospective study collected 85 PC and 57 matched healthy controls (HC) to analyze microbial characteristics by MiSeq sequencing. The results showed that gut microbial diversity was decreased in PC with an unique microbial profile, which partly attributed to its decrease of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
184
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(221 citation statements)
references
References 54 publications
11
184
0
7
Order By: Relevance
“…Bacteroidetes, Firmicutes, Proteobacteria, and Verrucomicrobia were the top dominant populations in the three groups, together accounting for up to 95% of sequences, in which the abundance and relationship between Bacteroidetes and Firmicutes significantly contributed to gut microbial composition and changes [45,46]. Notably, we found that phylum Bacteroidetes were decreased, while phyla Proteobacteria and Verrucomicrobia Cellular Physiology and Biochemistry…”
Section: Discussionmentioning
confidence: 69%
“…Bacteroidetes, Firmicutes, Proteobacteria, and Verrucomicrobia were the top dominant populations in the three groups, together accounting for up to 95% of sequences, in which the abundance and relationship between Bacteroidetes and Firmicutes significantly contributed to gut microbial composition and changes [45,46]. Notably, we found that phylum Bacteroidetes were decreased, while phyla Proteobacteria and Verrucomicrobia Cellular Physiology and Biochemistry…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, in liver cirrhosis, bacterial families like Enterobacteriaceae, Veillonellaceae and Streptococcaceae were found to be prevalent, with a decrease in beneficial populations such as Lachnospiraceae [53]. In a recent study by Ren et al, a miSeq analysis showed that some potential pathogens like Veillonella, Klebsiella, and Selenomonas and LPS-producing bacteria including Prevotella, Hallella, and Enterobacter were enriched in pancreatic adenocarcinoma, whereas probiotics including Bifidobacterium and some butyrateproducing bacteria, such as Coprococcus, Clostridium IV, Blautia, Flavonifractor and Anaerostipes were reduced [54].…”
Section: Discussionmentioning
confidence: 99%
“…Pötgens et al demonstrated on a murine model that Klebsiella oxytoca behaves as a gut pathobiont, that is, it increases gut permeability, and thus influences cancer progression [78]. Ren et al demonstrated a significant decrease in commensal Bifidobacterium and butyrate-producing bacteria such as Coprococcus, Clostridium IV, Blautia, Flavonifractor, and Anaerostipes in PDAC patients [79]. These data suggest that enrichment in Gram-negative bacteria with a decrease in butyrate producers is positively correlated with pancreatic cancer development.…”
Section: Microflora In Pancreatic Adenocarcinomamentioning
confidence: 99%